2023
DOI: 10.1111/cen.14944
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular bone score and bone mineral density as indices of skeletal fragility in endogenous Cushing's syndrome

Hiya Boro,
Velmurugan Mannar,
Rakhi Malhotra
et al.

Abstract: Objective: Endogenous Cushing's syndrome (CS) is a known cause of secondary osteoporosis. Vertebral fractures (VFs) in endogenous CS may occur despite normal bone mineral density (BMD). Trabecular bone score (TBS) is a relatively new, noninvasive technique to assess bone microarchitecture. The objective of our study was to analyse the BMD and bone microarchitecture using TBS in endogenous CS and compare it with a group of age and sex-matched healthy controls, and also analyse the factors predicting BMD and TBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Rahaman et al [18] found a negative correlation with morning serum cortisol and BMD at LS (r 2 = 0.09, P = 0.08) and hip (r 2 = 0.09, P = 0.09), although this is not statistically significant. Likewise, Boro et al [1] reported that BMD at the L1-L4 level showed significant negative correlations with plasma cortisol at 8 a.m. (Spearman's rho ρ = -.397, p =.011).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Rahaman et al [18] found a negative correlation with morning serum cortisol and BMD at LS (r 2 = 0.09, P = 0.08) and hip (r 2 = 0.09, P = 0.09), although this is not statistically significant. Likewise, Boro et al [1] reported that BMD at the L1-L4 level showed significant negative correlations with plasma cortisol at 8 a.m. (Spearman's rho ρ = -.397, p =.011).…”
Section: Discussionmentioning
confidence: 88%
“…Similarly, femoral neck BMD also had significant positive correlations with weight and BMI (femoral neck BMD; ρ =.590, p <.001 for weight and ρ =.503, p <. 001 for BMI) [1].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Novel tools for assessing bone quality and resistance have recently emerged as having added value for predicting fractures in various forms of osteoporosis [ 42 , 43 ]. So far, some of these tools have also been tested as fracture predictors in osteopathies driven by pituitary hyperfunction [ 44 ] and specifically in acromegaly, since they could possibly overcome the abovementioned limitations of areal DXA evaluation in patients affected by this disease [ 45 ]. Briefly, bone quality in acromegaly has been assessed by high-resolution peripheral quantitative computed tomography (HR-pQCT), a three-dimensional noninvasive imaging technique that scans the extremities and can assess volumetric bone density and microarchitecture of cortical and cancellous bone [ 46 ].…”
Section: Methods For the Evaluation Of Bone Healthmentioning
confidence: 99%